GEOMETRIC ELEMENTS TEACHING - A METHODOLOGY FOR ENHANCING CREATIVITY THROUGH 3D MODELING AND INNOVATIVE EDUCATIONAL TECHNOLOGIES (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the methodological potential of innovative educational technologies for increasing learners’ creativity in the teaching of geometric elements through 3D modeling. The relevance of the topic is determined by the transition of school education toward digital, competence-based, and practice-oriented instruction, where spatial reasoning, design thinking, and creative problem solving are regarded as core learning outcomes. The paper synthesizes contemporary international findings on 3D modeling, virtual environments, and mathematical creativity, and correlates them with the digital transformation agenda of Uzbekistan’s education system. Particular attention is given to the pedagogical conditions under which 3D modeling becomes not merely a visualization tool but a medium for productive inquiry, experimentation, and divergent thinking. The study argues that the most effective methodology is based on staged integration of digital visualization, collaborative project work, interactive assessment, and reflective design tasks. The proposed methodological model can be adapted for primary and lower secondary mathematics education and may serve as a conceptual basis for future empirical classroom research.